Steel slag-based composite cementing material as well as preparation method and application thereof
By modifying steel slag powder and adding stabilizer, combined with the combination of water-quenched blast furnace slag powder, gypsum and silica fume, the concrete expansion and crack problems caused by free calcium oxide in steel slag are solved, and the effect of improving the stability, strength and economic benefits of concrete is achieved.
Patent Information
- Application Number
- CN202411857455.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-11
AI Technical Summary
When the free calcium oxide contained in steel slag is hydrated in concrete, it will produce calcium hydroxide with a larger specific surface area, causing the concrete to expand and crack, affecting stability.
By modifying the steel slag powder, the content of free calcium oxide is reduced, and stabilizer is added to the raw materials, combined with the combination of water-quenched blast furnace slag powder, gypsum and silica fume, it forms extremely insoluble ettringite, promotes reaction, and generates a large amount of active silicone oxygen tetrahedron and C-S-H gels, improving the density and strength of concrete.
It effectively reduces the adverse impact of concrete stability, improves the strength and durability of concrete, and at the same time reduces the amount of cement, and improves economic benefits.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to a steel slag-based composite cementitious material and a preparation method and application thereof. Background Art
[0002] Steel slag is usually a by-product produced in the metallurgical process. If steel slag is used in concrete to replace part of the cement in concrete, the amount of cement used can be reduced and the cost of concrete can be reduced. At the same time, steel slag has a high content of elements such as silicon, aluminum, and calcium. These elements can play a good filling and doping role in concrete, thereby improving the quality and performance of concrete.
[0003] However, steel slag usually also contains free calcium oxide. The Ca(OH)2 generated by free calcium oxide is different from the Ca(OH)2 generated by cement hydration. The Ca(OH)2 generated by free calcium oxide has a larger specific surface area or volume, which can easily cause concrete expansion and cracks, thereby adversely affecting the stability of concrete. Summary of the invention
[0004] In order to reduce the adverse effects on the stability of concrete, the present application provides a steel slag-based composite cementitious material and a preparation method and application thereof.
[0005] In the first aspect, the present application provides a steel slag-based composite cementitious material, which adopts the following technical solution: A steel slag-based composite cementitious material and a preparation method and application thereof, comprising the following raw materials in parts by weight: 60-70 parts of modified steel slag powder, 15-25 parts of water-quenched blast furnace slag powder, 2-8 parts of gypsum, 2-8 parts of silica fume, and 4-6 parts of stabilizer.
[0006] By adopting the above technical solution, the modified steel slag powder, water-quenched blast furnace slag powder, gypsum, silica fume and stabilizer are mixed evenly, and the free calcium oxide content in the modified steel slag powder obtained after the modification treatment is reduced, thereby reducing the possibility of volume expansion of calcium hydroxide formed by the free calcium oxide, and the stabilizer is added to the raw materials to further improve the stability of the modified steel slag powder, thereby further reducing the adverse effect on the stability of the obtained concrete; The hydration process of dicalcium silicate, tricalcium silicate and other components in modified steel slag powder is similar to that of minerals in concrete, and both produce products such as CSH gel. In addition, the active components in modified steel slag powder are stimulated in the alkaline environment generated by cement hydration, and further react. The generated hydration products fill the pores, increase the density of the concrete system, and thus improve the strength and durability of the concrete. Water-quenched blast furnace slag powder, modified steel slag powder and gypsum are selected for compounding and synergistic use, wherein the water-quenched blast furnace slag powder provides calcium ions and aluminum ions, the modified steel slag powder provides divalent metal cations and hydroxide ions, and the gypsum provides calcium ions and sulfate ions, which together form extremely insoluble calcium sulfonate, promote the continuous reaction, and at the same time promote the depolymerization of silicon-oxygen tetrahedrons and aluminum-oxygen tetrahedrons in the water-quenched blast furnace slag powder and the modified steel slag powder, so that a large number of active silicon-oxygen tetrahedrons appear in the system, thereby combining with calcium ions in the liquid phase in the form of a single silicate ion or a polymer of multiple silicate ions to form more and more CSH gels, which is convenient for reducing the amount of minerals added in the concrete system and improving the utilization rate of the water-quenched blast furnace slag powder and the modified steel slag powder; Moreover, the seed effect, volcanic ash effect and micro-aggregate filling effect of silica fume and the relatively highly active alumina tetrahedron in water-quenched blast furnace slag can synergistically enhance the hydration reaction in the highly alkaline liquid phase system of modified steel slag powder, so that more CSH gel and AFt crystals are generated in the composite cementitious system. The CSH gel tightly wraps the AFt crystals, and the two grow in an interlaced manner to form a complex and dense network structure, thereby improving the mechanical properties of the cementitious material and further stimulating the cementitious activity of the steel slag.
[0007] Preferably, the modified steel slag powder is hot-melt steel slag powder after digestion treatment, and the digestion treatment method of the steel slag powder comprises the following steps: Water and hot-melt steel slag are added into the slag pool in a weight ratio of (3-4):10. After digestion for 20±2h, the steel slag is filtered out to obtain modified steel slag powder.
[0008] By adopting the above technical scheme, the hot-melt steel slag powder is suffocated and digested with water in the above ratio, and the hot-melt steel slag is suddenly cooled and broken. At this time, the free calcium oxide in the hot-melt steel slag reacts with water to generate calcium hydroxide, and is separated from the modified steel slag powder by filtration, thereby effectively reducing the content of free calcium oxide in the hot-melt steel slag, reducing the activity of the modified steel slag powder, and improving the stability of the modified steel slag powder, thereby reducing the possibility of volume expansion of calcium hydroxide generated by free calcium oxide during the hydration process, and reducing the adverse effect on the stability of concrete; when the ratio of water to hot-melt steel slag is less than the above ratio, it is easy to cause the amount of free calcium oxide in the hot-melt steel slag that reacts with water to be reduced and difficult to fully remove; when the ratio of water to hot-melt steel slag exceeds the above ratio, it is easy to cause the possibility of waste of water resources.
[0009] Preferably, the stabilizer is prepared by mixing ethylene glycol and diphenylmethane diisocyanate in a weight ratio of 2:(2-4).
[0010] By adopting the above technical scheme, ethylene glycol and diphenylmethane diisocyanate are added in the above ratio, ethylene glycol first reacts with free calcium oxide in the modified steel slag powder to generate ethylene glycol calcium, and diphenylmethane diisocyanate reacts with water to generate carbon dioxide, which reacts with free calcium oxide to generate calcium carbonate, and at the same time, carbon dioxide gas is generated to react with the generated ethylene glycol calcium to generate calcium carbonate and ethylene glycol, which further facilitates the removal of free calcium oxide from the modified steel slag powder, improves the stability of the modified steel slag powder, and further reduces the impact on the prepared mixture. The adverse effect on the stability of concrete; when the ratio of ethylene glycol and diphenylmethane diisocyanate exceeds the above ratio, the content of ethylene glycol increases, which may make it difficult for the carbon dioxide produced by diphenylmethane diisocyanate to fully react with the generated ethylene glycol calcium and the free calcium oxide in the modified steel slag powder, affecting the removal rate of free calcium oxide; when the ratio of ethylene glycol and diphenylmethane diisocyanate exceeds the above ratio, the content of ethylene glycol decreases, making it difficult to fully remove the free calcium oxide in the modified steel slag powder, affecting the stability of concrete.
[0011] Preferably, the diphenylmethane diisocyanate is a modified diphenylmethane diisocyanate, which is prepared from diphenylmethane diisocyanate and attapulgite in a weight ratio of 1:(4-6), and the modified diphenylmethane diisocyanate is prepared by the following steps: The attapulgite is heated to 300±10°C under a nitrogen atmosphere for activation for 2±1h and then dried. The activated attapulgite is added to an anhydrous toluene solution of diphenylmethane diisocyanate according to a weight ratio, dispersed at room temperature for 10-20min under a nitrogen atmosphere, heated to 60-100°C for reaction for 0.5-1.5h, cooled naturally, washed and filtered to obtain modified diphenylmethane diisocyanate.
[0012] By adopting the above technical scheme, attapulgite is selected to modify diphenylmethane diisocyanate, so that diphenylmethane diisocyanate is grafted on the surface of attapulgite without changing the fibrous morphology of the attapulgite, and at the same time the dispersibility of the attapulgite is improved, so that diphenylmethane diisocyanate produces silicon dioxide and removes free calcium oxide. At the same time, the attapulgite makes it difficult for the prepared steel slag-based composite cementitious material to settle when added to concrete, thereby improving the strength of the concrete in various places and further reducing the adverse effects on the stability of the concrete.
[0013] In a second aspect, the present application provides a method for preparing a steel slag-based composite cementitious material, using the following technical solution: A method for preparing a steel slag-based composite cementitious material comprises the following steps: S1. Grinding: Mix modified steel slag powder, water-quenched blast furnace slag powder, gypsum and stabilizer according to weight ratio and grind for 0.5-1min. The grinding pressure is 10-13MPa. During grinding, water is added at 30-70kg / min, and hot air is introduced. The hot air speed is 9±1m / s and the hot air temperature is 300±10℃ to obtain a mixture. S2. Mixing: Add silica fume to the mixture prepared in S1 according to a weight ratio and mix well to prepare a steel slag-based composite cementitious material.
[0014] By adopting the above technical scheme, the modified steel slag powder, water-quenched blast furnace slag powder, gypsum and stabilizer are mixed and ground, so that the modified steel slag powder is easy to crush. Similarly, water is added during grinding to increase the contact area between the free calcium oxide in the modified steel slag powder and the water and stabilizer, which is further convenient for removing the free calcium oxide in the modified steel slag powder and reducing the possibility of concrete cracking. In addition, hot air is introduced during the grinding process to facilitate drying the raw materials without affecting the removal of the free calcium oxide.
[0015] Preferably, the specific surface area of the mixture obtained in step S1 is 530-600m 2 / kg.
[0016] By adopting the above technical scheme, the mixture is ground to a specific surface area within the above range. At this time, the hydration rate of raw materials such as modified steel slag powder increases after grinding, the lattice defects increase, the surface energy increases, and the activity increases, thereby increasing the rate at which the obtained concrete slurry forms a spatial network structure, shortening the setting time, and producing a large amount of hydration products to improve the density of the obtained concrete slurry, thereby increasing the flexural and compressive strengths; when the specific surface area of the mixture is less than the above range, it is easy to cause the setting time of the obtained concrete to increase and the flexural and compressive strengths to decrease; when the specific surface area of the mixture is greater than the above range, it is easy to increase the grinding cost and reduce the economic benefits.
[0017] In a third aspect, the present application provides a concrete prepared by using a steel slag-based composite cementitious material, using the following technical solution: A concrete prepared by using a steel slag-based composite cementitious material comprises the following steps: The steel slag-based composite cementitious material, cement, coarse aggregate and fine aggregate are mixed to obtain a dry mix, and water is added to the dry mix to mix well to obtain concrete.
[0018] By adopting the above technical scheme, the prepared steel slag-based composite cementitious material is mixed with cement, coarse aggregate and fine aggregate, and water is added to mix them to obtain concrete. At this time, the free calcium oxide content in the steel slag-based composite cementitious material is low, which reduces the adverse effect on the stability of the prepared concrete, while reducing the amount of cement used and improving economic benefits.
[0019] Preferably, the content of the steel slag-based composite cementitious material in the concrete is 1-2%.
[0020] By adopting the above technical scheme, when the steel slag-based composite cementitious material in the above range is added, the setting time of the prepared concrete is shorter, and the flexural and compressive strengths are enhanced; when the added amount of the steel slag-based composite cementitious material is less than the above range, it is easy to cause the possibility of increased cement consumption, affecting the economic benefits; when the added amount of the steel slag-based composite cementitious material is greater than the above range, due to the slow initial hydration rate of the steel slag, it is easy to cause the possibility of increased setting time of the prepared concrete, and at the same time, due to the reduction of early cementitious hydration products, it is easy to cause the possibility of higher slurry porosity, affecting the flexural and compressive strengths of the prepared concrete.
[0021] In summary, this application has the following beneficial effects: 1. Mix the modified steel slag powder, water-quenched blast furnace slag powder, gypsum, silica fume and stabilizer. At this time, the free calcium oxide content in the modified steel slag powder obtained after the modification treatment is reduced, and the possibility of volume expansion of calcium hydroxide formed by free calcium oxide is reduced. In addition, the stabilizer is added to the raw materials to further improve the stability of the modified steel slag powder and further reduce the adverse effect on the stability of the obtained concrete.
[0022] 2. The hot-melt slag powder is steamed and digested, and the hot-melt slag is cooled suddenly and broken. At this time, the free calcium oxide in the hot-melt slag reacts with water to form calcium hydroxide, which is separated from the modified steel slag powder by filtration, thereby effectively reducing the content of free calcium oxide in the hot-melt steel slag, reducing the activity of the modified steel slag powder, and improving the stability of the modified steel slag powder, thereby reducing the possibility of volume expansion of calcium hydroxide generated by free calcium oxide during the hydration process.
[0023] 3. Ethylene glycol first reacts with free calcium oxide in the modified steel slag powder to generate ethylene glycol calcium, and diphenylmethane diisocyanate reacts with water to generate carbon dioxide, which reacts with free calcium oxide to generate calcium carbonate. At the same time, carbon dioxide gas is generated to react with the generated ethylene glycol calcium to generate calcium carbonate and ethylene glycol, which further facilitates the removal of free calcium oxide from the modified steel slag powder, improves the stability of the modified steel slag powder, and further reduces the adverse effect on the stability of the prepared concrete. DETAILED DESCRIPTION
[0024] The present application is further described in detail below in conjunction with embodiments.
[0025] The 7-day activity index detection method, 28-day activity index detection method, free calcium oxide content detection method and stability detection method in all embodiments and comparative examples are as follows: 1.7-day activity index The 7-day activity index of steel slag-based composite cementitious materials was tested according to the testing method of national standard GB / T 20491-2017 "Steel slag powder used in cement and concrete".
[0026] 2.28 days activity index The 28-day activity index of steel slag-based composite cementitious materials was tested according to the testing method of national standard GB / T 20491-2017 "Steel slag powder used in cement and concrete".
[0027] 3. Free calcium oxide content The free calcium oxide content of steel slag-based composite cementitious materials was tested according to the national standard YB / T 4328-2012 "Determination of free calcium oxide content in steel slag".
[0028] 4. Stability The stability of steel slag-based composite cementitious materials is tested according to the national standard GB / T 1346-2011 "Test methods for water consumption, setting time and stability of cement of standard consistency".
[0029] raw material The raw materials in all the examples of the present application can be obtained from commercial sources, wherein attapulgite is of industrial grade and diphenylmethane diisocyanate is of analytical grade.
[0030] Preparation Example Preparation Example 1 Modified steel slag powder Preparation Example 1.1 A modified steel slag powder is prepared by the following steps: 30 kg of water and 100 kg of hot-melt steel slag were added into the slag pool. After digestion for 20 hours, the steel slag was filtered out to obtain modified steel slag powder.
[0031] Preparation Example 1.2 Different from Preparation Example 1.1, the amount of water added in Preparation Example 1.2 is 35 kg.
[0032] Preparation Example 1.3 Different from Preparation Example 1.1, the amount of water added in Preparation Example 1.3 is 40 kg.
[0033] Preparation Example 2 Modified diphenylmethane diisocyanate Preparation Example 2.1 A modified diphenylmethane diisocyanate is prepared by the following steps: 4 kg of attapulgite was heated to 300°C under a nitrogen atmosphere for activation for 2 hours and then dried. The activated attapulgite was added to 1 kg of anhydrous toluene solution of diphenylmethane diisocyanate, dispersed at room temperature for 10 minutes under a nitrogen atmosphere, heated to 60°C for reaction for 0.5 hours, cooled naturally, washed and filtered to obtain modified diphenylmethane diisocyanate.
[0034] Preparation Example 2.2 Different from Preparation Example 2.1, the dispersion time in Preparation Example 2.2 is 15 min, the reaction temperature is 80° C., and the reaction time is 1 h.
[0035] Preparation Example 2.3 Different from Preparation Example 2.1, the dispersion time in Preparation Example 2.3 is 20 min, the reaction temperature is 100° C., and the reaction time is 1.5 h.
[0036] Preparation Example 2.4 Different from Preparation Example 2.2, the amount of attapulgite added in Preparation Example 2.4 is 5 kg.
[0037] Preparation Example 2.5 Different from Preparation Example 2.2, the amount of attapulgite added in Preparation Example 2.5 is 6 kg.
[0038] Preparation Example 3 Stabilizer Preparation Example 3.1 A stabilizer is prepared by mixing 3 kg of ethylene glycol and 3 kg of diphenylmethane diisocyanate. Preparation Example 3.2 Different from Preparation Example 3.1, the amount of ethylene glycol added in Preparation Example 3.2 is 2.4 kg, and the amount of diphenylmethane diisocyanate added is 3.6 kg.
[0039] Preparation Example 3.3 Different from Preparation Example 3.1, the amount of ethylene glycol added in Preparation Example 3.3 is 2 kg, and the amount of diphenylmethane diisocyanate added is 4 kg.
[0040] Preparation Examples 3.4-3.8 Different from Preparation Example 3.2, in Preparation Examples 3.4-3.8, an equal amount of modified diphenylmethane diisocyanate obtained in Preparation Examples 2.1-2.5 was used to replace diphenylmethane diisocyanate.
[0041] Example Example 1 Raw material ratio Example 1.1 A steel slag-based composite cementitious material is prepared by the following steps: S1. Grinding: 60 kg of modified steel slag powder from Preparation Example 1.1, 25 kg of water-quenched blast furnace slag powder, 8 kg of gypsum and 4 kg of stabilizer from Preparation Example 3.1 were mixed and ground for 0.5 min. The grinding pressure was 10 MPa. Water was added at 30 kg / min during grinding. Hot air was introduced at a speed of 9 m / s and a temperature of 300 °C to obtain a mixture. The specific surface area of the ground mixture was 530 m2 / kg; S2. Mixing: Add 2 kg of silica fume to the mixture prepared in S1 and mix well to prepare a steel slag-based composite cementitious material.
[0042] Examples 1.2-1.5 Different from Example 1.1, the raw material ratios and process parameters in Examples 1.2-1.5 are different, see Table 1 for details.
[0043] Table 1 Raw material ratios and process parameters of Examples 1.1-1.5
[0044] Comparative Example 1 The difference from Example 1.1 is that in Comparative Example 1, an equal amount of steel slag is used to replace the modified steel slag powder.
[0045] Comparative Example 2 Different from Example 1.1, no stabilizer was added in Comparative Example 2.
[0046] The 7-day activity index, 28-day activity index, free calcium oxide content and stability of the steel slag-based composite cementitious materials prepared in Examples 1.1-1.5 and Comparative Examples 1-2 were tested, as shown in Table 2.
[0047] Table 2 Performance test data table
[0048] Combined with Table 2, it can be seen that the steel slag-based composite cementitious materials prepared in Examples 1.1-1.5 are better than those in Comparative Example 1 in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the use of modified steel slag powder in Examples 1.1-1.5 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious materials while reducing the free calcium oxide content.
[0049] The steel slag-based composite cementitious materials prepared in Examples 1.1-1.5 performed better than those in Comparative Example 2 in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This indicates that adding stabilizers to the raw materials in Examples 1.1-1.5 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious materials while reducing the free calcium oxide content.
[0050] The influence of the preparation process of steel slag-based composite cementitious materials was investigated in Examples 1.1-1.3. The results showed that the steel slag-based composite cementitious materials prepared in Example 1.2 performed better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This indicates that the grinding time, grinding pressure, water addition rate and specific surface area of the mixture after grinding selected in Example 1.2 are beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious materials while reducing the free calcium oxide content.
[0051] Taking Example 1.2 as a control, the influence of the raw material ratio of the steel slag-based composite cementitious material was investigated in Examples 1.4-1.5. The results showed that the steel slag-based composite cementitious material prepared in Example 1.4 performed better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the raw material ratio of the steel slag-based composite cementitious material selected in Example 1.4 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0052] Example 2 Modified steel slag powder Examples 2.1-2.2 Different from Example 1.4, the modified steel slag powder in Examples 2.1-2.2 comes from Preparation Examples 1.2-1.3 in equal amounts.
[0053] The 7-day activity index, 28-day activity index, free calcium oxide content and stability of the steel slag-based composite cementitious material prepared in Examples 2.1-2.2 were tested, as shown in Table 3.
[0054] Table 3 Performance test data table
[0055] Combined with Table 3, it can be seen that, with Example 1.4 as a control, Examples 2.1-2.2 investigated the influence of the ratio of water to hot-melt steel slag during the water-steaming digestion of the modified steel slag powder. The results showed that the steel slag-based composite cementitious material obtained in Example 2.2 performed better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the ratio of water to hot-melt steel slag during the water-steaming digestion of the modified steel slag powder selected in Example 2.2 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the obtained steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0056] Example 3 Stabilizer Examples 3.1-3.7 Different from Example 2.1, the stabilizers in Examples 3.1-3.7 are respectively obtained in equal amounts from Preparation Examples 3.2-3.8.
[0057] The 7-day activity index, 28-day activity index, free calcium oxide content and stability of the steel slag-based composite cementitious materials prepared in Examples 3.1-3.7 were tested, as shown in Table 4.
[0058] Table 4 Performance test data table
[0059] Combined with Table 4, it can be seen that, with Example 2.2 as a control, the influence of the ratio of stabilizer raw materials in Examples 3.1-3.2 is studied. The results show that the steel slag-based composite cementitious material prepared in Example 3.1 performs better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the stabilizer raw material ratio selected in Example 3.1 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0060] Using Example 3.1 as a control, Examples 3.3-3.7 investigated the influence of modified diphenylmethane diisocyanate. The results showed that by replacing diphenylmethane diisocyanate with an equal amount of modified diphenylmethane diisocyanate in Examples 3.3-3.7, the steel slag-based composite cementitious material obtained had better performance in 7-day activity index, 28-day activity index, free calcium oxide content and stability than Example 3.1. This shows that the use of modified diphenylmethane diisocyanate to prepare the stabilizer in Examples 3.3-3.7 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0061] In Examples 3.3-3.5, the effects of dispersion time, reaction temperature and reaction time when preparing modified diphenylmethane diisocyanate were investigated. The results showed that the steel slag-based composite cementitious material prepared in Example 3.4 performed better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the dispersion time, reaction temperature and reaction time selected in Example 3.4 are beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0062] Taking Example 3.4 as a control, the influence of the raw material ratio of modified diphenylmethane diisocyanate was investigated in Examples 3.6-3.7. The results showed that the steel slag-based composite cementitious material prepared in Example 3.6 performed better in terms of 7-day activity index, 28-day activity index, free calcium oxide content and stability. This shows that the raw material ratio of modified diphenylmethane diisocyanate selected in Example 3.6 is beneficial to improving the 7-day activity index, 28-day activity index and stability of the prepared steel slag-based composite cementitious material while reducing the free calcium oxide content.
[0063] The density, water content, sulfur trioxide content and chloride ion content of the steel slag-based composite cementitious materials prepared in Examples 1-3 were tested according to the testing method of the national standard GB / T 20491-2017 "Steel slag powder used in cement and concrete". It was found that the density of the steel slag-based composite cementitious materials prepared in Examples 1-3 was ≥3.2g / cm², the water content was ≤1.0%, the sulfur trioxide content was ≤4.0%, and the chloride ion content was ≤0.06%, which met the production requirements of the steel slag-based composite cementitious materials.
[0064] Application Examples Application Example 1 Addition Amount of Steel Slag-based Composite Materials Application Example 1.1 A concrete weighing 2500 kg is prepared by the following steps: The steel slag-based composite cementitious material from Example 1.1, cement, coarse aggregate and fine aggregate were mixed to prepare a dry mix, and water was added to the prepared dry mix and mixed to prepare concrete, in which the content of the steel slag-based composite cementitious material was 30 kg.
[0065] Application Example 1.2 Different from Application Example 1.1, the content of steel slag-based composite cementitious material in Application Example 1.2 is 40 kg.
[0066] Application Example 1.3 Different from Application Example 1.1, the content of steel slag-based composite cementitious material in Application Example 1.3 is 50 kg.
[0067] Application Example 2 Application Examples 2.1-2.13 Different from Application Example 1.2, the steel slag-based composite cementitious materials in Application Examples 2.1-2.13 are in equal amounts from Examples 1.2-3.7.
[0068] Comparative Application Example 1-2 Different from Application Example 1, an equal amount of the steel slag-based composite cementitious material in Comparative Application Examples 1-2 comes from Comparative Examples 1-2.
[0069] The following performance test experiments were conducted on the concrete prepared in Application Example 1-2 and Comparative Application Example 1-2. The performance test experiments included the stability, flexural strength and compressive strength of the concrete. The test data are shown in Table 5.
[0070] 1. Stability The stability of the prepared concrete is tested according to the national standard GB / T 1346-2011 "Test methods for water consumption, setting time and stability of cement of standard consistency".
[0071] 2.7d flexural strength and 28d flexural strength According to the national standard GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 7d flexural strength and 28d flexural strength of the prepared concrete were tested. Testing environment: 22℃.
[0072] 3.7d compressive strength and 28d compressive strength According to the national standard GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 7d compressive strength and 28d compressive strength of the prepared concrete were tested. Testing environment: 22℃.
[0073] Table 5 Performance test data of application example 1-2 and comparative application example 1-2
[0074] The following describes the present application in detail in conjunction with the test data provided in Table 5.
[0075] Combining the comparative application examples 1-2 and the application examples 1-2, it was found that the concrete prepared by the application examples 1-2 of the present application performed better than the concrete prepared by the comparative application examples 1-2 in terms of stability, flexural strength and compressive strength. This indicates that the steel slag-based composite cementitious material of the present application performs better in improving the stability, flexural strength and compressive strength of concrete.
[0076] Combining Application Example 1.1 and Comparative Application Example 1, it can be found that the concrete obtained by replacing the modified steel slag powder with an equal amount of steel slag in Comparative Application Example 1 is worse than that in Application Example 1.1 in terms of stability, flexural strength and compressive strength. This shows that the use of modified steel slag powder in Application Example 1.1 of this application is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0077] Combining Application Example 1.1 and Comparative Application Example 2, it can be found that no stabilizer was added in Comparative Application Example 2, and the performance of the prepared concrete in terms of stability, flexural strength and compressive strength were all worse than those in Application Example 1.1. This shows that adding a stabilizer to the raw materials of Application Example 1.1 of this application is beneficial to improving the stability, flexural strength and compressive strength of the concrete.
[0078] Application Examples 1.1-1.3 investigated the effect of the amount of steel slag-based composite cementitious materials added to concrete. The results showed that the concrete prepared in Application Example 1.2 performed better in terms of stability, flexural strength and compressive strength. This shows that the amount of steel slag-based composite cementitious materials selected in Application Example 1.2 is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0079] Taking Application Example 1.2 as a control, the influence of the preparation process of steel slag-based composite cementitious materials was investigated in Application Examples 2.1-2.2. The results showed that the concrete prepared in Application Example 2.1 performed better in terms of stability, flexural strength and compressive strength. This shows that the process parameters for preparing steel slag-based composite cementitious materials selected in Application Example 2.1 are beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0080] Taking Application Example 2.1 as a control, Application Examples 2.3-2.4 investigated the influence of the raw material ratio of steel slag-based composite cementitious materials. The results showed that the concrete prepared in Application Example 2.3 performed better in terms of stability, flexural strength and compressive strength. This shows that the raw material ratio of steel slag-based composite cementitious materials selected in Application Example 2.3 is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0081] Taking Application Example 2.3 as a control, the influence of the preparation process of modified steel slag powder was investigated in Application Examples 2.5-2.6. The results showed that the concrete prepared in Application Example 2.5 performed better in terms of stability, flexural strength and compressive strength. This shows that the ratio of water and hot-melt steel slag used in the preparation of modified steel slag powder in Application Example 2.5 is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0082] Taking Application Example 2.5 as a control, Application Examples 2.7-2.8 investigated the influence of the raw material ratio of the stabilizer. The results showed that the concrete prepared in Application Example 2.7 performed better in terms of stability, flexural strength and compressive strength. This shows that the raw material ratio of the stabilizer selected in Application Example 2.7 is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0083] Taking Application Example 2.7 as a control, the influence of the preparation process of modified diphenylmethane diisocyanate was investigated in Application Examples 2.9-2.11. The results showed that the concrete prepared in Application Example 2.10 performed better in terms of stability, flexural strength and compressive strength. This shows that the process parameters for preparing modified diphenylmethane diisocyanate selected in Application Example 2.10 are beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0084] Taking Application Example 2.10 as a control, Application Examples 2.12-2.13 investigated the influence of the raw material ratio of modified diphenylmethane diisocyanate. The results showed that the concrete prepared in Application Example 2.12 performed better in terms of stability, flexural strength and compressive strength. This shows that the raw material ratio of modified diphenylmethane diisocyanate selected in Application Example 2.12 is beneficial to improving the stability, flexural strength and compressive strength of concrete.
[0085] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A steel slag-based composite cementitious material, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of modified steel slag powder, 15-25 parts of water-quenched blast furnace slag powder, 2-8 parts of gypsum, 2-8 parts of silica fume, and 4-6 parts of stabilizer.
2. The steel slag-based composite cementitious material according to claim 1, characterized in that: The modified steel slag powder is hot-melt steel slag powder that has been digested, and the digestion treatment method of the steel slag powder comprises the following steps: Water and hot-melt steel slag are added into the slag pool in a weight ratio of (3-4):
10. After digestion for 20±2h, the steel slag is filtered out to obtain modified steel slag powder.
3. The steel slag-based composite cementitious material according to claim 2, characterized in that: The stabilizer is prepared by mixing ethylene glycol and diphenylmethane diisocyanate in a weight ratio of 2:(2-4).
4. The steel slag-based composite cementitious material according to claim 3, characterized in that: The diphenylmethane diisocyanate is a modified diphenylmethane diisocyanate, which is prepared from diphenylmethane diisocyanate and attapulgite in a weight ratio of 1:(4-6), and the modified diphenylmethane diisocyanate is prepared by the following steps: The attapulgite is heated to 300±10°C under a nitrogen atmosphere for activation for 2±1h and then dried. The activated attapulgite is added to an anhydrous toluene solution of diphenylmethane diisocyanate according to a weight ratio, dispersed at room temperature for 10-20min under a nitrogen atmosphere, heated to 60-100°C for reaction for 0.5-1.5h, cooled naturally, washed and filtered to obtain modified diphenylmethane diisocyanate.
5. A method for preparing the steel slag-based composite cementitious material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Grinding: Mix modified steel slag powder, water-quenched blast furnace slag powder, gypsum and stabilizer according to weight ratio and grind for 0.5-1min. The grinding pressure is 10-13MPa. During grinding, water is added at 30-70kg / min, and hot air is introduced. The hot air speed is 9±1m / s and the hot air temperature is 300±10℃ to obtain a mixture. S2. Mixing: Add silica fume to the mixture prepared in S1 according to a weight ratio and mix well to prepare a steel slag-based composite cementitious material.
6. The method for preparing a steel slag-based composite cementitious material according to claim 5, characterized in that: The specific surface area of the mixture prepared in step S1 is 530-600 m2 / kg.
7. A concrete made by using a steel slag-based composite cementitious material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The steel slag-based composite cementitious material, cement, coarse aggregate and fine aggregate are mixed to obtain a dry mix, and water is added to the dry mix to mix well to obtain concrete.
8. A concrete according to claim 7, characterized in that: The content of the steel slag-based composite cementitious material in the concrete is 1-2%.
Citation Information
Cited By
High-performance additive and steel slag doped cementing material applied to high-performance additive
CN120518346A
A steel slag-based cementitious material suitable for silty soil in the Yellow River floodplain and an in-situ pile construction method
CN122562365A